Noblestitch® system for PFO closure: A novel but judicious alternative to traditional devices—A case report - Onorato, Eustaquio Maria; Grancini, Luca; Monizzi, Giovanni; Mastrangelo, Angelo; Fabbiocchi, Franco; Bartorelli, Antonio L. (Frontiers in Cardiovascular Medicine, 2023)
Background Percutaneous suture-mediated patent foramen ovale (PFO) closure has recently been used with the aim of avoiding double-disc nitinol device implantation. This novel technique has been carried out successfully in several centers offering PFO closure with an effective closure rate comparable to conventional double-disc devices. Case summary A 50-year-old man, a pentathlon athlete, suffering from a previous left-sided ischemic stroke, underwent percutaneous closure of a permanent right-to-left shunt via PFO with a large fenestrated septum primum aneurysm at another institution. The NobleStitch® system was successfully implanted using local anesthesia and under angiographic-fluoroscopic monitoring. He was discharged home on aspirin 100 mg daily with a moderate residual shunt on contrast transthoracic echocardiography (cTTE) that persisted unaltered at subsequent controls. After 7 months, unable to resume sporting activity because of physical discomfort and dyspnea on exertion, the patient asked for a second opinion at our Heart and Brain clinic. Two-dimensional (2D) TTE showed septum primum laceration next to a radiopaque polypropylene knot with a moderate bidirectional shunt located at the fenestrated septum primum far from the PFO site. A catheter-based closure of the septal defect was therefore planned under local anesthesia and rotational intracardiac echo monitoring. An equally sized discs 28.5 mm × 28.5 mm Flex II UNI occluder (Occlutech GmbH, Jena, Germany) was successfully implanted across the atrial septal defect without complications. The patient was discharged in good clinical conditions; dual antiplatelet therapy (aspirin 100 mg/daily and clopidogrel 75 mg/daily) was recommended for 2 months and then single antiplatelet therapy (aspirin100 mg/daily) up to 6 months. Abolition of the residual shunt was confirmed at 1- and 6-month follow-up by contrast transcranial Doppler and 2D color Doppler cTTE. Discussion Closing a PFO with a suture-base system, without leaving a device implant behind, may be a cutting-edge technology and potential alternative to traditional devices. Nevertheless, meticulous selection of the PFO anatomies by 2D TEE is key to a successful closure procedure in order to avoid complications that must be managed again with a second percutaneous procedure or by surgery.